Integrated skills approach in the English learning as a foreing language - Quishpe Hipo, Luis (mktDESCUBRE; Vol 1 No 19 (2022): Nineteenth Edition (January - June), 2022)
Nowadays, English language constitutes a key competence for permanent learning for lifelong to improve the personal development. The objective study was to identify the strategies of the ISA applied in the English classroom of the Environmental Engineering School, ESPOCH- Campus Macas, during the semester April – September 2021. The research approach was a qualitative and quantitative method called mixed. The basic modality was a field and bibliography research. The research design was non-experimental of the transversal design. The level of the research was descriptive. The population were made up of 30 students and the sample was probabilistic type. The survey was applied to identify the level of communication in English language of the students and the ISA strategies. As well as, a checklist was applied during the observation classroom to compare the students’ perception about the ISA strategies. The information was analyzing by descriptive statistic through frequency of distribution, and the results were presented by charts with percentage values. The results determined that the 93 % of the students develop the language skills in insolation way where prevalence the traditional strategies, and the 90 % of the students achieve a low level of the communicative competences. In conclusion, the strategies from ISA are directly corelated with the target language learning (L2).